Paper folding as a Mean to Produce Knowledge on Geometry - Santa Ramirez, Z. M.; Jaramillo Lopez, C. M.; De Carvalho Borba, M. [UNESP] (Fundacion Univ Catolica Norte, 2015)
Because of the formal nature which has been conferred to the teaching of geometry in the courses constituting the educational programs, during the research reported in this article has been noticed some difficulties of teachers for producing knowledge on geometry such as poor understanding of the basic concepts, among others. This scarcities become evident when the teachers must teach them in the basic levels of ed ucation. In this scenario, the study is aimed at analyzing the ways in which are created processes of production of knowledge on geometry in a group of teachers using paper folding, in such a way that this contribute to their professional development as teachers. Therefore, by means of a qualitative research, which is based on an educational activity involving paper folding, it is expected to show how this group of teachers, through their interactions, can produce knowledge on geometry in order to enhance their educational process.
Keywords: Group of teachers practicing paper folding; Production of knowledge; Human beings with means; Trisection of an acute angle